The Enforcement of Public Price Controls - Cox, Charles C. (Journal of Political Economy, 1980)
Price controls differ across industries systematically as predicted by the theory regulators maximize political support. This approach views the price controllers as choosing, subject to technology and budget constraints, the appropriate enforcement to balance the support from holding down prices against the opposition from dead-weight loss. Differences in enforcement depend on weights in the official price index, elasticities of supply and demand, and structural characteristics of industries. Data from the 1971-74 regime of price controls are used to test the theory. The empirical evidence clearly shows the predicted differences in price controls for a cross section of industries.